2020
DOI: 10.1007/s12325-020-01352-8
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab Use in Patients with Moderate to Severe Psoriasis, Psoriatic Arthritis and Ankylosing Spondylitis in Real-World Setting in Europe: Baseline Data from SERENA Study

Abstract: Introduction: Secukinumab, a fully human monoclonal antibody that directly inhibits interleukin-17A, has demonstrated robust efficacy in the treatment of moderate to severe psoriasis (PsO), psoriatic arthritis (PsA) and ankylosing spondylitis (AS), with a rapid onset of action, sustained long-term clinical responses and a consistently favourable safety profile across phase 3 trials. Here, we report the clinical data at enrolment from SERENA, designed to investigate the real-world use of secukinumab across all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 76 publications
4
28
0
Order By: Relevance
“…Additional studies would help to further elucidate the position of secukinumab in the real-world setting. The ongoing, longitudinal, observational SERENA study ( n = 2932) will assess the long-term (up to 5 years) retention of secukinumab in routine clinical practice across three indications (plaque psoriasis, AS and PsA) [ 62 ].…”
Section: Place Of Secukinumab In the Management Of Psoriatic Arthritismentioning
confidence: 99%
“…Additional studies would help to further elucidate the position of secukinumab in the real-world setting. The ongoing, longitudinal, observational SERENA study ( n = 2932) will assess the long-term (up to 5 years) retention of secukinumab in routine clinical practice across three indications (plaque psoriasis, AS and PsA) [ 62 ].…”
Section: Place Of Secukinumab In the Management Of Psoriatic Arthritismentioning
confidence: 99%
“…Some severe cases and exacerbations of Crohn's disease have also been described (8), so caution is recommended with its use. In terms of routine clinical practice, studies show a safety profile similar to that previously reported in RCTs and their long-term extension studies (9)(10)(11)(12), but information from real-world evidence studies is still scarce. Data on survival of biological therapy in PsA from the DANBIO registry showed a median survival of the first TNF inhibitor (TNFi) being 2.2 years and the second and third TNFi being 1.3 and 1.1 years, respectively.…”
Section: Introductionmentioning
confidence: 59%
“… 24 , 76 Here, we will focus on two key registries [EuroSpA and Consortium of Rheumatology Researchers of North America (CORRONA)] and studies (AQUILA and SERENA). 77 80 …”
Section: Secukinumabmentioning
confidence: 99%